Clinical Coaching Cards: A Game of Active Learning Theory and Teaching Techniques - Bjorn Watsjold; Diana Zhong (Association of American Medical Colleges, 2020)
Introduction Clinical Coaching Cards is a serious game for faculty development in which players take turns as Teacher and Coach to apply teaching techniques on game cards to identify new approaches to teaching in the clinical environment. The game employs active learning theory and coaching frameworks. Methods Based on a literature search and local faculty practices, we identified 14 techniques for clinical teaching and created a deck of cards summarizing each. We adapted rules from social judgment games so that participants proposed and selected techniques for applicability to their own teaching. The game was presented as a subsession of larger faculty development workshops hosted by the University of Washington, and players included faculty, residents, and medical students. Evaluations focused on the applicability of techniques to participants' clinical practice and preferred new techniques. Results Seventy-four players provided evaluations out of over 150 participants across six workshops. Participants rated the session as mostly or very organized in 70 of 74 evaluations (95%), the introductory material as mostly or very relevant in 67 evaluations (91%), and the teaching techniques as most or several being useful in 69 evaluations (93%). Although some techniques were more popular than others, every technique was selected as a Top 3 technique for future practice. Discussion Clinical Coaching Cards is a card game that applies active learning within a framework of peer coaching to teach bedside and clinical teaching techniques.